THE DATA ACQUISITION ROLE ON STATIC TEST FOR VALIDATION OF RX320 ROCKET MOTOR DESIGN - Setiadi Setiadi; Bagus Wicaksono; Kurdianto Kurdianto; Bagus H. Jihad (Program Studi Fisika Universitas Negeri Jakarta, 2021)
Data Acquisition System has a significant role, especially in static testing of a rocket, determining whether a rocket is declared eligible to fly or not based on the static rocket test. Static testing of the RX320 rocket involves several numerical data instrumentation components, including the Yokogawa DL850 and the CDA900 Signal Conditioner, and the PT750 Pressure sensor. It has functions to accept the physical force that occurs, measure and record the value of the Pressure force in the RX 320 Rocket Chamber at the time Static test during burning time is performed. From the record value of the RX 320 chamber pressure, it can be stated that the RX 320 is suitable for the rocket flight test. The calculation results of the chamber pressure design and the results of measurement and recording of RX320 static test data indicate that the Pressure Chamber RX320 value is still within the safe limits of the RX320 Rocket motor tube material strength.